TAJEN & DESAKRALISASI PURA DI DESA PAKRAMAN SUBAGAN, KECAMATAN KARANGASEM, BALI - Diksyiantara, Ida Bagus Gede Eka; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT Tajen is a Balinese folk game which exists since a long time ago, however by throwing a bet in this game; it makes tajen very identical to gambling. Moreover it is performed in the temple and this effort will certainly give unfavorable impact on the sanctity of the temple in which it is used as a place to hold tajen, although tajen conducted at the Jaba Sisi (part the outer temple in the concept of tri mandala)still,itwillcause thetemplesuffereddesacralization. On the concept of Kekeran or Concept of the radius of the sanctity of the temple, Kekeran has three approach methods to determine the radius of the sanctity of the temple such as Apeneleg, Apenimpug, Apenyengker in which the most clearly measure as already stated by building a wall around the temple.For Pura Desa, it will usually use apenyengker method (wall boundary), it means the territory of Jaba sisi of the temple is the area that belongs to the sanctity of the temple area therefore for any reason, tajen which is performed in Jaba sisi temple area can reduce the sanctity of its temple. Keywords: Tajen,Temple,Kekeran,Desakralisasi.